Electrolyte and battery

By using the first additive of a specific structure in the lithium-ion battery electrolyte, the battery capacity attenuation problem caused by insufficient electrolyte infiltration is solved, and a more stable and denser interface film formation is achieved, which significantly improves the cycling performance and safety of the battery.

CN119742445AActive Publication Date: 2025-04-01EVE POWER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411924288.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Due to insufficient electrolyte infiltration, high-energy density lithium-ion batteries lead to accelerated battery capacity attenuation, which may even cause safety problems such as thermal runaway.

Method used

A specific first additive is used, and its general structure includes functional groups such as benzene ring, large π bond, ester group or carboxyl group as additives to reduce the surface tension of the electrolyte, promote the electrolyte to better infiltrate into the electrode material, and enhance the structural stability and thermal stability of the interface film through the formation of amine compounds.

Benefits of technology

By improving the wetting properties of the electrolyte and the formation of the interface mask, the circulation performance and safety of the battery are significantly improved, while maintaining high energy density, extending the battery's service life and reducing safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742445A_ABST
    Figure CN119742445A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a battery, and relates to the technical field of lithium ion batteries. The electrolyte comprises a first additive, a lithium salt and an organic solvent, the structure of the first additive is # imgabs0 #, R1, R2, R3 and R4 are independently selected from any one of hydrogen atoms, halogen atoms, alkyl groups, halogen atom substituted or unsubstituted alkyl groups, halogen atom substituted or unsubstituted alkoxy groups, halogen atom substituted or unsubstituted phenyl groups and cyano groups, and R1, R2, R3 and R4 are independently selected from any one of hydrogen atoms, halogen atoms, alkyl groups, halogen atom substituted or unsubstituted alkyl groups, halogen atom substituted or unsubstituted alkoxy groups, halogen atom substituted or unsubstituted phenyl groups and cyano groups. Or CR2R3 is a cyclopropyl group; r5 is selected from any one of hydrogen atoms, alkyl groups, halogen atom substituted or unsubstituted alkyl groups and cyano groups; r6 is selected from a hydrogen atom, or R6 is a carbonyl group and R6 is linked to an ortho-phenyl group with respect to an amide group. When the first additive is applied to the battery, the high energy density and the cycle performance of the battery can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte and a battery. Background Art

[0002] With the development of portable electronic devices and electric vehicles, consumers have also put forward higher requirements for the long service life of lithium-ion batteries. The energy density of the battery directly determines the duration of a single use. High energy density can provide a longer use time. At present, most of the energy density of the battery is improved by increasing the compaction density and surface density of the electrode sheet. However, the solvent system of the traditional electrolyte (such as carbonate solvents) at this stage has a high surface tension in the high-density electrode sheet and cannot effectively penetrate into the micropores of the electrode sheet. The electrolyte infiltration in some areas of the electrode sheet is insufficient, which affects the formation of the SEI film and the CEI film, and reduces the stability of the electrode-electrolyte interface. The unstable electrode-electrolyte interface will promote the continuous decomposition of the electrolyte on the electrode surface, resulting in the thickening of the interface film and the increase of lithium ion transmission resistance, which ultimately leads to accelerated battery capacity decay and may even cause safety problems such as thermal runaway. Summary of the invention

[0003] The main purpose of the present application is to provide an electrolyte and a battery to solve the problem of battery capacity attenuation due to insufficient electrolyte infiltration in high energy density batteries in the related art.

[0004] In order to achieve the above object, according to one aspect of the present application, a first additive is provided, and the first additive has a structure shown in general formula (I):

[0005]

[0006] Wherein, R1 and R4 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, a phenyl group substituted or unsubstituted by a halogen atom, and a cyano group;

[0007] R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, and a phenyl group substituted or unsubstituted by a halogen atom, or CR2R3 is a cyclopropyl group;

[0008] R5 is selected from any one of a hydrogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, and a cyano group;

[0009] R6 is selected from a hydrogen atom, or R6 is a carbonyl group and R6 is connected to the ortho-phenyl group relative to the amide group.

[0010] Further, R1 and R4 are each independently selected from any one of a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a C1-C12 alkyl group substituted or unsubstituted by a halogen atom, a C1-C12 alkoxy group substituted or unsubstituted by a halogen atom, a C6-C12 phenyl group substituted or unsubstituted by a halogen atom, and a cyano group;

[0011] R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, a C1-C12 alkyl group substituted or unsubstituted by a halogen atom, a C1-C12 alkoxy group substituted or unsubstituted by a halogen atom, and a C6-C12 phenyl group substituted or unsubstituted by a halogen atom, or CR2R3 is a cyclopropyl group.

[0012] Further, R1 is selected from any one of a hydrogen atom, a C1-C6 alkyl group, and a halogen atom-substituted or unsubstituted C1-C6 alkyl group;

[0013] R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, a C1-C6 alkyl group, a halogen atom-substituted or unsubstituted C1-C6 alkyl group, and a halogen atom-substituted or unsubstituted C6-C18 phenyl group; or CR2R3 is a cyclopropyl group;

[0014] R4 is selected from any one of a hydrogen atom, a C1-C6 alkyl group, a halogen atom-substituted or unsubstituted C1-C6 alkyl group, and a cyano group.

[0015] Further, R1 is selected from any one of a hydrogen atom and a C1-C3 alkyl group;

[0016] R2 and R3 are each independently selected from any one of a hydrogen atom, a fluorine atom, a C1-C3 alkyl group, and a C6 phenyl group; or CR2R3 is a cyclopropyl group;

[0017] R4 is selected from any one of a hydrogen atom, a C1-C4 alkyl group and a cyano group.

[0018] Furthermore, the first additive is selected from any one of Formula A1, Formula A2, Formula A3, Formula A4, and Formula A5:

[0019]

[0020]

[0021] Furthermore, the mass content of the first additive in the electrolyte is 0.5% to 3.0%;

[0022] Preferably, the mass content of the first additive in the electrolyte is 1% to 2.5%.

[0023] Further, the lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium borate, lithium difluorooxalatoborate, and lithium bis(fluorosulfonyl)imide;

[0024] Preferably, the lithium salt is lithium hexafluorophosphate or a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide;

[0025] More preferably, the lithium salt is a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, wherein the mass content of lithium hexafluorophosphate in the electrolyte is 11% to 12%, and the mass content of lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3%;

[0026] Preferably, the mass content of lithium salt in the electrolyte is 12% to 15%.

[0027] Further, the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite, ethyl acetate, diethyl sulfite, and 1,3-propane sultone;

[0028] Preferably, the organic solvent comprises at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;

[0029] More preferably, the organic solvent is a mixed solvent of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate, wherein the mass ratio of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate is (3-9):(0.1-4):(6-7):(4-6).

[0030] Further, the electrolyte further includes a second additive;

[0031] The second additive includes at least one of vinylene carbonate and vinyl sulfate.

[0032] Furthermore, the mass ratio of the first additive to the second additive is 1:(0.1-6).

[0033] Furthermore, the mass content of the second additive in the electrolyte is 0.5% to 3%.

[0034] According to a third aspect of the present application, a battery is provided, the battery comprising the electrolyte according to the second aspect.

[0035] Furthermore, the battery further comprises a negative electrode sheet containing a negative electrode active material; and / or,

[0036] The battery also includes a positive electrode sheet containing a positive electrode active material;

[0037] Preferably, the negative electrode active material comprises a carbon-based negative electrode material;

[0038] Preferably, the positive electrode active material includes lithium iron phosphate.

[0039] By applying the technical solution of the present application, a first additive having a specific general formula is applied to a battery as an electrolyte additive. On the one hand, the large π bond, ester group or carboxyl group of the benzene ring in the general formula of the first additive can reduce the surface tension of the electrolyte. The reduction of the surface tension is conducive to better infiltration of the electrolyte in the electrode material with high compaction density and high surface density, ensuring the uniform formation of the interface film and maintaining the efficient transmission of lithium ions. On the other hand, during the first charge and discharge process of the battery, the ester group or carboxyl group and amide group in the general formula of the first additive will react rapidly to form amine compounds, which will polymerize and cover the electrode surface, participate in the formation of the interface film, and enhance the structural stability of the interface film. In addition, the interface film of the nitrogen-containing compound also has good thermal stability, which is conducive to alleviating the damage of the interface film caused by the temperature rise of the battery. By applying the first additive to the battery, under the synergistic effect of the functional groups in the general structure, not only the wettability is enhanced, but also the formation of a more stable and denser interface film is promoted, thereby significantly improving the cycle performance and safety of the battery while maintaining the high energy density of the battery. DETAILED DESCRIPTION

[0040] As described in the background of the present application, there is a problem in the prior art that high energy density batteries suffer from battery capacity decay due to insufficient electrolyte infiltration. In order to solve the above problem, in the first aspect of the present application, an electrolyte is provided, the electrolyte comprising a first additive, a lithium salt and an organic solvent, wherein the first additive has a structure shown in general formula (I):

[0041]

[0042] Wherein, R1 and R4 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, a phenyl group substituted or unsubstituted by a halogen atom, and a cyano group;

[0043] R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, and a phenyl group substituted or unsubstituted by a halogen atom, or CR2R3 is a cyclopropyl group;

[0044] R5 is selected from any one of a hydrogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, and a cyano group;

[0045] R6 is selected from a hydrogen atom, or R6 is a carbonyl group and R6 is connected to the ortho-phenyl group relative to the amide group.

[0046] During the first charge and discharge process, the carboxyl group, ester group, and amide group will decompose rapidly to generate amine compounds and carbon dioxide (CO2). The nitrogen atom in the amine compound carries a lone pair of electrons. Due to the conjugation effect of the benzene ring, these lone pairs of electrons are attracted to the vicinity of the benzene ring, which promotes the polymerization of the amine compound. The polymerized amine compound forms a dense and stable interface film on the electrode surface, namely the solid electrolyte interface (SEI) film and the positive electrode electrolyte interface (CEI) film. The formation of the interface film prevents the electrode from directly contacting the electrolyte, effectively inhibits the continuous decomposition of the electrolyte, reduces the dissolution of metal ions, thereby reducing the side reactions inside the battery and improving the battery's cycle performance.

[0047] The interfacial film formed by nitrogen-containing compounds is not only dense, but also has good thermal stability. During the charging and discharging process, heat is generated inside the battery, and higher thermal stability can alleviate the damage of high temperature to the SEI film and maintain the integrity and stability of the film. In this way, not only can the safety of the battery be improved, but also the dead lithium phenomenon caused by high temperature can be reduced, that is, the lithium ions cannot return to their initial state during the charging and discharging process, thereby avoiding the rapid attenuation of the battery capacity and improving the battery's cycle performance.

[0048] Due to the presence of a large π bond, carboxyl or ester group in the benzene ring structure of general formula (I), the surface tension of the electrolyte is reduced. The reduction in surface tension is conducive to better infiltration of the electrolyte in electrode materials with high compaction density and high surface density, especially the infiltration of the surface of the graphite negative electrode, ensuring the uniform formation of the SEI film, maintaining the efficient transmission of lithium ions, and further improving the cycle performance of the battery.

[0049] Therefore, the first additive of the present application effectively solves the problem of insufficient wetting of high energy density lithium-ion batteries during the cycle by promoting the formation of SEI and CEI films, improving the thermal stability of the films and reducing the surface tension of the electrolyte. The introduction of this first additive not only improves the cycle performance of the battery, but also improves the safety and stability of the battery, so that the battery can still maintain excellent cycle performance under the conditions of high compaction density and high surface density of the electrode sheet.

[0050] In some embodiments, R1 and R4 are each independently selected from any one of hydrogen atom, halogen atom, C1-C12 alkyl, C1-C12 alkyl substituted or unsubstituted by halogen atom, C1-C12 alkoxy substituted or unsubstituted by halogen atom, C6-C12 phenyl substituted or unsubstituted by halogen atom, and cyano; R2 and R3 are each independently selected from any one of hydrogen atom, halogen atom, alkyl, C1-C12 alkyl substituted or unsubstituted by halogen atom, C1-C12 alkoxy substituted or unsubstituted by halogen atom, and C6-C12 phenyl substituted or unsubstituted by halogen atom, or CR2R3 is cyclopropyl. By further limiting the carbon number of the substituent, the cost and performance of the electrolyte can be balanced.

[0051] In some embodiments, R1 is selected from any one of hydrogen atom, C1-C6 alkyl, halogen atom substituted or unsubstituted C1-C6 alkyl; R2 and R3 are independently selected from any one of hydrogen atom, halogen atom, C1-C6 alkyl, halogen atom substituted or unsubstituted C1-C6 alkyl, halogen atom substituted or unsubstituted C6-C18 phenyl; or CR2R3 is cyclopropyl; R4 is selected from any one of hydrogen atom, C1-C6 alkyl, halogen atom substituted or unsubstituted C1-C6 alkyl, cyano. By further limiting the carbon number and type of the substituent, the performance of the electrolyte can be further improved.

[0052] In some embodiments, R1 is selected from any one of hydrogen atom and C1-C3 alkyl; R2 and R3 are independently selected from any one of hydrogen atom, fluorine atom, C1-C3 alkyl and C6 phenyl; or CR2R3 is cyclopropyl; R4 is selected from any one of hydrogen atom, C1-C4 alkyl and cyano. By further limiting the type of substituents, the wettability and thermal stability of the electrolyte can be further improved.

[0053] In some embodiments, the first additive is selected from any one of Formula A1, Formula A2, Formula A3, Formula A4, and Formula A5:

[0054]

[0055] By limiting the first additive to be selected from any one of the above structures, it is possible to further ensure the formation of a denser and more stable interface film, further improve the wettability of the electrolyte to the electrode material, and thus further take into account both high energy density and excellent cycle performance.

[0056] Due to the inclusion of the first additive having a specific structural formula, the electrolyte is applied to the battery, and under the synergistic effect of each component, not only the wettability is enhanced, but also the formation of a more stable and dense interface film is promoted, thereby significantly improving the cycle performance and safety of the battery while maintaining the high energy density of the battery. The electrolyte is suitable for lithium-ion batteries.

[0057] In some embodiments, the mass content of the first additive in the electrolyte is 0.5% to 3.0%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any two thereof. By limiting the mass content of the first additive to the above range, it is ensured that the first additive can play an effective role in the electrolyte to the maximum extent.

[0058] In some embodiments, the mass content of the first additive in the electrolyte is 1% to 2.5%. By limiting the mass content of the first additive to the above range, in addition to ensuring that the first additive can play an effective role in the electrolyte to the maximum extent, it also avoids possible side effects caused by excessive addition.

[0059] Lithium salt is the main source of conductive ions in the electrolyte. For example, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium borate (LiBOB), lithium difluorooxalate borate (LiODFB), and lithium bis(fluorosulfonyl)imide (LiFSI). In some embodiments, the lithium salt is lithium hexafluorophosphate or a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. When the lithium salt is a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the mass content of lithium hexafluorophosphate in the electrolyte is 11% to 12%, such as 11%, 11.5%, 12%, or a range consisting of any two thereof, and the mass content of lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or a range consisting of any two thereof.

[0060] The present application does not limit the specific amount of lithium salt added, which can be adjusted according to actual needs. In some embodiments, the mass content of lithium salt in the electrolyte is 12% to 15%, such as 12%, 13%, 14%, 15% or any two thereof.

[0061] The organic solvent is a major component of the electrolyte and is responsible for transporting lithium ions. In some embodiments, the organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene sulfite (PS), ethyl acetate (EP), diethyl sulfite (DES), and 1,3-propane sultone (1,3-PS).

[0062] The present application does not limit the amount of organic solvent added, as long as the mass content of the above-mentioned additives and lithium salts meets the above-mentioned requirements, the remaining components can be organic solvents, as long as the sum of the mass content of each component is 100%.

[0063] The organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. By limiting the organic solvent within the above range, the transmission of lithium ions is facilitated. For example, in some embodiments, the organic solvent is a mixed solvent of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate, wherein the mass ratio of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate is (3-9): (0.1-4): (6-7): (4-6). By limiting the specific type and mass ratio of the organic solvent, the chemical stability, wettability, lithium ion conductivity, battery internal resistance, safety, life, energy density, and cost-performance balance of the electrolyte can be optimized, thereby significantly improving the overall performance of the lithium-ion battery.

[0064] In some embodiments, the electrolyte further includes a third additive. The third additive can improve the wettability of the electrolyte to the high surface density electrode material, ensure that the electrolyte can fully penetrate into the electrode material, improve the transmission efficiency of lithium ions, and thus help maintain the good performance of the battery at high energy density. In addition, the third additive helps to form a thin and stable SEI film, reducing the ineffective volume expansion of the battery during the cycle.

[0065] The present application does not limit the specific type of the third additive, and it can be a conventional third additive in the art. For example, in some embodiments, the third additive includes vinyl sulfate (ES).

[0066] In some embodiments, the mass content of the third additive in the electrolyte is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any two thereof.

[0067] In some embodiments, the electrolyte further includes a second additive, and the second additive includes at least one of vinylene carbonate (VC) and vinyl sulfate (ES). The second additive can promote the formation of a SEI film on the surface of the negative electrode, and the formation of the SEI film can reduce the formation of lithium dendrites and the direct oxidation of the negative electrode material, thereby reducing the risk of battery short circuit and further improving the cycle performance and safety of the battery.

[0068] The second additive has a high oxidation potential, good chemical stability and thermal stability. By adding the second additive, the volatility of the electrolyte can be optimized, the volatilization of the electrolyte at high temperature or during charging and discharging can be reduced, and the thermal stability of the battery can be enhanced. It is especially suitable for devices that require high power output and improves the overall safety of the battery. Therefore, by introducing the second additive, under the joint action of lithium salt, the second additive and the first additive, the composition of the electrolyte can be further optimized, and the cycle performance of the battery can be further improved.

[0069] In some embodiments, the mass ratio of the first additive to the second additive is 1:(0.1-6), for example, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or a range consisting of any two thereof.

[0070] In some embodiments, the mass content of the second additive in the electrolyte is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any two thereof.

[0071] The present application does not limit the specific preparation method of the electrolyte, as long as it contains the above components. For example, the specific preparation method of the electrolyte includes the following steps: adding an electrolyte additive, a third additive, and a second additive to an organic solvent under a protective atmosphere, then adding a lithium salt, stirring and mixing at a first temperature to obtain an electrolyte; wherein the protective atmosphere can be argon gas, and the first temperature can be 5 to 15°C.

[0072] A third aspect of the present application provides a battery, the battery comprising the electrolyte provided in the second aspect.

[0073] Due to the inclusion of the above-mentioned electrolyte, the battery has excellent cycle performance, especially maintaining a high capacity retention rate at high energy density. In addition, the battery can meet the needs of different temperature scenarios.

[0074] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material and disposed on the surface of the negative electrode current collector.

[0075] When preparing the negative electrode sheet, the negative electrode active material, the first conductive agent, and the first binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70% to 99% of graphite negative electrode material, 0.5% to 15% of the first conductive agent, and 0.5% to 15% of the first binder in terms of mass percentage.

[0076] Among them, the material of the negative electrode current collector can be at least one of copper foil, nickel foam, and copper foam; the first conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the first binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.

[0077] The present application does not limit the specific type of negative electrode active material in the negative electrode sheet, and it can be a negative electrode active material commonly used in current batteries, such as at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, and silicon-based negative electrode materials. In some embodiments, the negative electrode active material includes a carbon-based negative electrode material.

[0078] The positive electrode sheet includes a positive electrode collector and a positive electrode active layer formed of a positive electrode active material and disposed on the surface of the positive electrode collector.

[0079] When preparing the positive electrode sheet, the positive electrode active material, the second conductive agent, and the second binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the positive electrode active layer includes 70% to 99% of the positive electrode active material, 0.5% to 15% of the second conductive agent, and 0.5% to 15% of the second binder in terms of mass percentage.

[0080] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the second conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the second binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.

[0081] The present application does not limit the specific type of positive electrode active material in the positive electrode sheet, and it can be a positive electrode active material commonly used in current batteries, such as at least one composite oxide of lithium and metals of cobalt, nickel, manganese and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium iron phosphate, lithium nickel manganese oxide, and lithium-rich manganese-based materials. In some embodiments, the positive electrode active material includes lithium iron phosphate.

[0082] The battery also includes a diaphragm. The present application does not limit the specific selection of the diaphragm material, and it can be a diaphragm material commonly used in batteries, such as a polypropylene diaphragm, a polyethylene diaphragm, a polypropylene / polyethylene double-layer composite diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite diaphragm, etc.

[0083] When preparing the battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain the battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte is injected into the dry battery. After the battery is aged, formed and sealed for the second time, the battery preparation is completed.

[0084] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0085] Example 1

[0086] The electrolyte of this embodiment includes 1.0% of the compound shown in formula A1 (CAS No. 918409-37-7), 3% of vinylene carbonate (VC), 11.5% of lithium hexafluorophosphate (LiPF6) and 1.0% of lithium bis(fluorosulfonyl)imide (LiFSI) according to the mass content of 100%, and the balance is an organic solvent; wherein the organic solvent is a mixed organic solvent of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a mass ratio of 5:1:8:6. The specific components of the electrolyte can be seen in Table 1.

[0087]

[0088] Example 2

[0089] The difference from Example 1 is that the compound represented by Formula A1 is replaced by an equal mass of the compound represented by Formula A2 (CAS No. 178872-52-1).

[0090]

[0091] Example 3

[0092] The difference from Example 1 is that the compound represented by formula A1 is replaced by an equal mass of the compound represented by formula A3 (CAS No. 112979-49-4).

[0093]

[0094] Example 4

[0095] The difference from Example 1 is that the compound represented by Formula A1 is replaced by an equal mass of the compound represented by Formula A4 (CAS No. 915302-77-1).

[0096]

[0097] Example 5

[0098] The difference from Example 1 is that the compound represented by formula A1 is replaced by an equal mass of the compound represented by formula A5 (CAS No. 541547-40-4).

[0099]

[0100] Example 6

[0101] The only difference from Example 1 is that LiFSI is not added, the organic solvent is used to make up to 100%, and the contents of other components are the same as in Example 1.

[0102] Example 7

[0103] The only difference from Example 1 is that LiFSI is replaced by LiPO2F2.

[0104] Example 8

[0105] The only difference from Example 1 is that the organic solvent is composed of ethylene carbonate and dimethyl carbonate in a mass ratio of 3:7.

[0106] Example 9

[0107] The difference from Example 1 is that the mass content of the compound represented by Formula A1 is 0.5%, which is supplemented to 100% by organic solvent, and the contents of other components are the same as in Example 1.

[0108] Example 10

[0109] The difference from Example 1 is that the mass content of the compound represented by Formula A1 is 2.5%, which is reduced to 100% by organic solvent, and the contents of other components are the same as in Example 1.

[0110] Embodiment 11

[0111] The difference from Example 1 is that the mass content of the compound represented by Formula A1 is 3%, which is reduced to 100% by organic solvent, and the contents of other components are the same as in Example 1.

[0112] Example 12

[0113] The difference from Example 1 is that the mass content of VC is 0.5%, which is supplemented to 100% by organic solvent, and the contents of other components are the same as those in Example 1.

[0114] Example 13

[0115] The difference from Example 1 is that VC is replaced by vinyl sulfate (ES).

[0116] Comparative Example 1

[0117] The only difference from Example 1 is that the compound represented by Formula A1 is not added, the organic solvent is used to make up to 100%, and the contents of other components are the same as in Example 1.

[0118] Comparative Example 2

[0119] The only difference from Example 1 is that the compound represented by formula A1 is not added, and the VC content is increased to 4.0%. The contents of other components are the same as in Example 1.

[0120] Comparative Example 3

[0121] The only difference from Example 1 is that the compound represented by formula A1 is replaced by a mixture of additives represented by formula B1, additives represented by formula B2, and additives represented by formula B3; wherein the mass ratio of the additives represented by formula B1, additives represented by formula B2, and additives represented by formula B3 is 1:1:1.

[0122]

[0123] Comparative Example 4

[0124] The only difference from Example 1 is that the compound represented by Formula A1 is replaced by the additive represented by Formula C (CAS No.: 16118-22-2).

[0125]

[0126] Comparative Example 5

[0127] The only difference from Example 1 is that the compound represented by Formula A1 is replaced by the additive represented by Formula D (CAS: 90914-57-1).

[0128]

[0129] Comparative Example 6

[0130] The only difference from Example 1 is that the compound represented by Formula A1 is replaced by the additive represented by Formula E (CAS: 61402-69-5).

[0131]

[0132] Comparative Example 7

[0133] The only difference from Example 1 is that the compound represented by Formula A1 is replaced by the additive represented by Formula F (CAS: 55577-65-6).

[0134]

[0135] Test example

[0136] 1. Preparation of batteries

[0137] Preparation of positive electrode sheet: prepare a glue solution with a solid content of 1.327%, add lithium iron phosphate, conductive agent Super-P, and N-methylpyrrolidone (NMP) to revolve at 25r / min, disperse at 500r / min, stir for 10min, then revolve at 25r / min, disperse at 1000r / min, and stir at 45°C for 90min; then add conductive agent carbon nanotube slurry, revolve at 25r / min, disperse at 1000r / min, vacuum degree 0.080kPa, stir at 45°C for 60min; then add glue solution, revolve at 25r / min, disperse at 2500r / min, and stir at 45°C for 60min. in, vacuum degree 0.080kPa, stirring at 45℃ for 90min; then adding NMP to adjust the slurry viscosity; finally, slowly stirring and revolving at 15r / min, dispersing at 500r / min, vacuum degree 0.080KPa, stirring for 0.5h to cool down, ensuring that the positive electrode discharge viscosity is 20000mPa·s, and the fineness is ≤15μm. In each step, the deposited materials on the stirring cylinder wall and the stirring rod are scraped in time, and the positive electrode sheets are obtained through screening, coating, cold pressing and slitting, wherein the mass ratio of lithium iron phosphate, conductive agent Super-P, carbon nanotubes and binder polyvinylidene fluoride is 95.0:2.0:0.5:2.5;

[0138] Preparation of negative electrode sheet: prepare a glue with a solid content of 8%, add graphite and conductive agent Super-P for dry mixing, rotate at 20r / min, disperse at 1000r / min, and stir for 1h; then add 50% negative electrode slurry, rotate at 20r / min, disperse at 1000r / min, and stir for 1.5h; add another 50% negative electrode glue, rotate at 25r / min, disperse at 2000r / min, vacuum at 0.085kPa, and stir for 1h; then add deionized water to adjust the slurry viscosity; finally add water-based dispersant styrene-butadiene latex, rotate at 25r / min, disperse at 800r / min, vacuum at 0.085KPa, and stir for 1h. The viscosity of the negative electrode material is guaranteed to be 4000mPa·s, and the fineness is ≤20μm. The deposited materials on the wall of the stirring cylinder and the stirring rod are scraped in time at each step. The negative electrode sheet is obtained through screening, coating, cold pressing and slitting. The mass ratio of the negative electrode active material graphite, the conductive agent Super-P, the thickener sodium carboxymethyl cellulose, and the adhesive styrene-butadiene latex is 95.5:1.5:1.2:1.8;

[0139] Preparation of lithium-ion battery: The prepared positive electrode sheet, negative electrode sheet and separator are subjected to a lamination process to obtain a bare battery cell, and the battery cell is loaded into an aluminum-plastic film packaging shell, and the electrolyte of the above-mentioned embodiment and comparative example is injected, and then sealing, standing, hot and cold pressing, formation and capacity separation processes are carried out to obtain a lithium-ion battery. The model of the lithium-ion battery is square aluminum shell 105Ah, the capacity distribution at room temperature is 107~110Ah, the energy density is 210~212Wh / kg, the voltage range of charge and discharge is 2.5~3.2V, and it supports continuous cycling at 1C rate.

[0140] 1. Internal resistance test

[0141] Use a multimeter to test the internal resistance of a fresh lithium-ion battery and record it.

[0142] 2. Electrochemical test

[0143] The following electrochemical tests were performed using a Xinwei charge and discharge test cabinet.

[0144] (1) Normal temperature cycle performance test:

[0145] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times under the above conditions.

[0146] Capacity retention rate (%) of a lithium-ion battery after 1000 cycles = (discharge capacity at the 1000th cycle / initial discharge capacity) × 100%.

[0147] Volume expansion rate (%) of a lithium-ion battery after 1000 cycles = (battery thickness at the 1000th cycle - initial battery thickness) / initial battery thickness × 100%.

[0148] (2) High temperature cycle performance test

[0149] At 45°C, the lithium-ion battery was charged at a constant current of 1.0C (nominal capacity) to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of ≤0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery was charged and discharged 1000 times under the above conditions.

[0150] Capacity retention rate (%) of a lithium-ion battery after 1000 cycles = (discharge capacity at the 1000th cycle / initial discharge capacity) × 100%.

[0151] Volume expansion rate (%) of a lithium-ion battery after 1000 cycles = (battery thickness at the 1000th cycle - initial battery thickness) / initial battery thickness × 100%.

[0152] The test results are shown in Table 2.

[0153] Table 1

[0154]

[0155]

[0156] Table 2

[0157]

[0158]

[0159] According to Table 1 and Table 2, by comparing Examples 1 to 13 and Comparative Examples 1 to 7, the present application can significantly improve the capacity retention rate and reduce the expansion rate after 1000 cycles under normal temperature and high temperature conditions by introducing a first additive with a specific structural formula.

[0160] It can be seen from Table 2 that Examples 1 to 5 have similar room temperature and high temperature cycle performance, and the volume expansion of the battery is small. Among them, the battery provided by Example 1 has the best comprehensive performance, and is significantly improved compared with Comparative Example 1. It can be seen that the first additive with a specific general formula provided by the present invention is added to the electrolyte to significantly improve the battery performance. The reason is that the interface film formed by the amine compound can effectively isolate the reaction between the electrolyte and the electrode interface. At the same time, this interface film also has good thermal stability, which inhibits the volume expansion of the battery during the cycle, thereby improving the high temperature cycle performance of the battery.

[0161] By comparing Examples 1, 6, and 7, it is found that since the LiPO2F2 lithium salt can also form a film on the negative electrode surface, when used in combination with the first compound of formula A1, the assembled battery can comprehensively improve the high-temperature cycle performance of the battery with less impedance growth. By comparing Examples 1 and 8, it is found that the addition of dimethyl carbonate DMC, a solvent with a relatively low viscosity, is conducive to reducing the internal resistance of the battery, thereby improving the comprehensive performance of the lithium iron phosphate battery under a high-density system.

[0162] By comparing Examples 1, 9, 10, and 11, it is found that the amount of Formula A1 has an optimal range of use, and the optimal performance is achieved when the amount is 1.0%. Although a small amount is added, it is beneficial to reduce the internal resistance, it is unable to form a sufficiently dense interface film, and the electrolyte and the electrode material continue to react, resulting in a decrease in cycle performance. A high amount of addition will form an overly thick interface film, increasing the internal resistance.

[0163] By comparing Example 1 with Comparative Example 3, it can be seen that the positive electrode film-forming additive disclosed in the prior art is not suitable for the lithium iron phosphate system. However, the first compound with a specific structure proposed in the present invention can be more easily oxidized to form a film at the negative electrode in the lithium iron phosphate system.

[0164] By comparing Example 1 with Comparative Examples 4, 5, 6, and 7, it can be seen that additives containing only a single benzene ring, amide group, carboxyl group, or ester group cannot achieve the same improvement in battery cycle performance as the use of Formula A1. The reason is that the various groups in Formula A1 have a synergistic effect, which can not only adapt to batteries with high compaction density design, but also form a more stable and dense interface film, inhibit volume expansion, and show excellent cycle performance.

[0165] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises a first additive, a lithium salt and an organic solvent, wherein the first additive has a structure shown in general formula (I): Wherein, R1 and R4 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, a phenyl group substituted or unsubstituted by a halogen atom, and a cyano group; R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, an alkoxy group substituted or unsubstituted by a halogen atom, and a phenyl group substituted or unsubstituted by a halogen atom, or CR2R3 is a cyclopropyl group; R5 is selected from any one of a hydrogen atom, an alkyl group, an alkyl group substituted or unsubstituted by a halogen atom, and a cyano group; R6 is selected from a hydrogen atom, or R6 is a carbonyl group and R6 is connected to the ortho-phenyl group relative to the amide group.

2. The electrolyte according to claim 1, characterized in that R1 and R4 are each independently selected from any one of a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a C1-C12 alkyl group substituted or unsubstituted by a halogen atom, a C1-C12 alkoxy group substituted or unsubstituted by a halogen atom, a C6-C12 phenyl group substituted or unsubstituted by a halogen atom, and a cyano group; R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, an alkyl group, a C1-C12 alkyl group substituted or unsubstituted by a halogen atom, a C1-C12 alkoxy group substituted or unsubstituted by a halogen atom, and a C6-C12 phenyl group substituted or unsubstituted by a halogen atom, or CR2R3 is a cyclopropyl group.

3. The electrolyte according to claim 2, characterized in that R1 is selected from any one of a hydrogen atom, a C1-C6 alkyl group, and a halogen atom-substituted or unsubstituted C1-C6 alkyl group; R2 and R3 are each independently selected from any one of a hydrogen atom, a halogen atom, a C1-C6 alkyl group, a halogen atom-substituted or unsubstituted C1-C6 alkyl group, and a halogen atom-substituted or unsubstituted C6-C18 phenyl group; or CR2R3 is a cyclopropyl group; R4 is selected from any one of a hydrogen atom, a C1-C6 alkyl group, a halogen atom-substituted or unsubstituted C1-C6 alkyl group, and a cyano group.

4. The electrolyte according to claim 3, characterized in that R1 is selected from any one of a hydrogen atom and a C1-C3 alkyl group; R2 and R3 are each independently selected from any one of a hydrogen atom, a fluorine atom, a C1-C3 alkyl group, and a C6 phenyl group; or CR2R3 is a cyclopropyl group; R4 is selected from any one of a hydrogen atom, a C1-C4 alkyl group and a cyano group.

5. The electrolyte according to any one of claims 1 to 4, characterized in that The first additive is selected from any one of Formula A1, Formula A2, Formula A3, Formula A4, and Formula A5:

6. The electrolyte according to any one of claims 1 to 5, characterized in that The mass content of the first additive in the electrolyte is 0.5% to 3.0%; Preferably, the mass content of the first additive in the electrolyte is 1% to 2.5%.

7. The electrolyte according to any one of claims 1 to 5, characterized in that The lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium borate, lithium difluorooxalatoborate, and lithium bis(fluorosulfonyl)imide; Preferably, the lithium salt is lithium hexafluorophosphate or a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; More preferably, the lithium salt is a mixed lithium salt of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, wherein the mass content of the lithium hexafluorophosphate in the electrolyte is 11% to 12%, and the mass content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3%; Preferably, the mass content of the lithium salt in the electrolyte is 12% to 15%; and / or, The organic solvent comprises at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite, ethyl acetate, diethyl sulfite, and 1,3-propane sultone; Preferably, the organic solvent comprises at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; More preferably, the organic solvent is a mixed solvent of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate, wherein the mass ratio of the ethylene carbonate, the propylene carbonate, the ethyl methyl carbonate and the dimethyl carbonate is (3 to 9): (0.1~4):(6~7):(4~6)。 8. The electrolyte according to any one of claims 1 to 7, characterized in that The electrolyte further includes a second additive; The second additive includes at least one of vinylene carbonate and vinyl sulfate; Preferably, the mass content of the second additive in the electrolyte is 0.5% to 3%.

9. A battery, characterized in that: The battery comprises the electrolyte according to any one of claims 1 to 8.

10. The battery according to claim 9, characterized in that The battery further comprises a negative electrode sheet containing a negative electrode active material; and / or, The battery also includes a positive electrode sheet containing a positive electrode active material; Preferably, the negative electrode active material comprises a carbon-based negative electrode material; Preferably, the positive electrode active material includes lithium iron phosphate.

Citation Information

Patent Citations

  • Composition for electrolyte of lithium secondary battery, gel polymer electrolyte, and lithium secondary battery including gel polymer electrolyte

    CN116114098A

  • Lithium ion battery electrolyte and lithium ion battery thereof

    CN116454384A

  • Electrolyte additive, electrolyte containing additive and battery

    CN118538999A

  • Smart system for optimal fermentation of IoT and AI based fermented foods

    KR102503771B1

  • Composition for electrolyte of lithium secondary battery, gel polymer electrolyte, and lithium secondary battery including gel polymer electrolyte

    US20230299343A1